Zinc Finger-Homeodomain Transcription Factor: A New Player in Plant Growth, Stress Response, and Quality Regulation - An-Qing Shen; Mei-Yan Lv; Yan-Xin Ge; Jin Zhou; Zhen-Zhu Hu; Xu-Qin Ren; Ai-Sheng Xiong; Guang-Long Wang (Agronomy)
Zinc finger-homeodomain (ZF-HD) transcription factors are a unique class that only exist in plants and are essential for plant growth and development, various stress responses, and quality formation and regulation. In recent years, an increasing number of reports regarding this class of transcription factors have been published, identifying their novel functions. In this paper, the evolution, structural characteristics, and subfamily classification of ZF-HD transcription factors are comprehensively introduced and the roles of the ZF-HD in abiotic and biotic stress responses, plant hormone signal transduction, and quality regulation are extensively investigated. In future studies, more efforts should be focused on the in-depth exploration of the mechanisms through which the ZF-HD could act at various stages of plant growth and development. We also determine the current research status and future directions related to the ZF-HD, with the aim of providing a comprehensive knowledge base and research insights for the further exploration of ZF-HD transcription factors in plant molecular biology.